Realizing Dignity for Enhancing Intercultural Competence - Breunig, Steven (HERMES - Journal of Language and Communication in Business, 2014)
The aim of this paper is to present the concept of dignity as a refl ective concept that may serve as a strategy for enhancing intercultural competence. Within the field of intercultural communication, intercultural competence seeks to impart essential knowledge and skills for engaging in intercultural encounters with cognitive, behavioral and affective competence. Dignity contributes to intercultural competence by enabling persons to view the social world anew. In this paper, dignity is conceptualized as the development and self-expression of persons free from social categorization, while acknowledging human vulnerability towards the social and material world. In intercultural encounters, a person may indeed sense their vulnerability due to a lack of social orientation, cultural awareness and language skills. Simultaneously, the vulnerability of the Other may be neglected with implications for effective and appropriate interaction between a Self and a culturally dissimilar Other. Accordingly, it is proposed that emotional regulation is essential for realizing dignity as an aspect of intercultural competence. Research on social dynamics and identity and the emotions is not without its precedence within intercultural communication. This project contributes to the objectives of intercultural communication and competence by theorizing how awareness of social dynamics and emotional regulation may support the realization of dignity during intercultural encounters. Dignity may complement other strategies related to cognitive, behavioral and affective competence for engaging in effective and appropriate communication.